Answer: y = -10
============================================================
Explanation:
There are two ways to solve this.
The first way is to divide both sides by -3 and then subtract 5 from both sides
-3(y+5) = 15
(-3(y+5))/(-3) = 15/(-3) ... divide both sides by -3
y+5 = -5
y+5-5 = -5-5 ... subtract 5 from both sides
y = -10
-----------------
Or we can distribute first, then add 15 to both sides, and finally divide both sides by -3
-3(y+5) = 15
-3(y)-3(5) = 15 ... distribute
-3y-15 = 15
-3y-15+15 = 15+15 ... add 15 to both sides
-3y = 30
-3y/(-3) = 30/(-3) ... divide both sides by -3
y = -10
Either way we get the same answer
-----------------
Let's check the answer
-3(y+5) = 15
-3(-10+5) = 15 ... replace y with -10
-3(-5) = 15
15 = 15
We get a true equation at the end after plugging in y = -10, so we have confirmed the answer